Original paperPatch test results in patients with allergic contact dermatitis in the Podlasie region - Reduta, Teresa; Bacharewicz, Joanna; Pawłoś, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : The aim of the study was to provide current data on the incidence of allergy to various contact allergens in patients with allergic contact eczema and the analysis of selected socio-demographic data of the patients. Material and methods : The study included 1532 patients (1010 women and 522 men) treated for allergic contact dermatitis at the Department of Dermatology and Venereology and at the Dermatology Outpatient Clinic in Bialystok in 2007–2011. The assessment of selected demographic data and skin lesions was based on the MOAHFLA index, while the results of patch tests were analyzed with modified Baseline European Series consisting of 31 allergens. Results : In the group of patients with eczema, 34.1% were men, and 55% of all respondents were people over 40 years of age. The occupational character of skin lesions was found in 22.5%. Most frequently (38.9%) skin lesions were localized on the hands, rarely involved legs (3.98%). Atopic dermatitis was diagnosed in 4.5% of patients. The ten most frequent allergens were: nickel sulfate (24%), cobalt chloride (15.3%), fragrance mix (8.25%), potassium dichromate (6.8%), balsam of Peru (5.5%), neomycin (4.42%), paraphenylenediamine (3.85%), Quatermium-15 (2.1%), detreomycin (1.83%) and budesonide (1.44% of tested patients). Conclusions : Frequent allergy to detreomycin indicates the need of patch testing for this allergen of all examined patients with allergic contact dermatitis. The increased frequency of the nickel allergy is a worrying problem and indicates the need for education about the risk factors for nickel allergy development and the implementation of appropriate legal regulations.